PERBANDINGAN PERHITUNGAN MASA PAJAK PENGHASILAN PASAL 21 PP 80/2010 DAN PP 58/2023 BAGI TENAGA AHLI BAPENDADKI JAKARTA - Keilan Rezkia Mumtaazah; Mohammad Benny Alexandri (Universitas Serang Raya, 2025)
Government Regulation Number 58 Year 2023 regulates changes in the calculation of Income Tax Article 21 effective January 1, 2024, replacing the calculation previously regulated in Government Regulation Number 80 Year 2010. This study aims to determine how the comparison of the calculation of Income Tax Article 21 Government Regulation Number 80 of 2010 and Government Regulation Number 58 of 2023 for experts of the DKI Jakarta Provincial Revenue Agency. The method used in this research is a qualitative method with a descriptive approach. The results showed that Income Tax Article 21 withheld using Government Regulation Number 80 of 2010 has a smaller amount of tax when compared to taxes withheld using Government Regulation Number 58 of 2023. However, if more than one layer of tariff is imposed on Government Regulation No. 80 of 2010, the Article 21 Income Tax withheld is greater than the tax using Government Regulation No. 58 of 2023. Although there is a change in the calculation of periodic Income Tax Article 21, this does not change the amount of annual Income Tax Article 21. This change has an impact on the income received monthly, the amount of Income Tax Article 21 period, and the amount of tax borne by personal taxpayers at the end of the tax year. Keyword: Income Tax, Income Tax Expense in Article 21, Average Effective Rate